Improving Soil Quality with Intercropping System: Corn (Zea (Mays) and Soybeans (Glycine max) - Feri Agriani; Sri Oktika Syahputri; Fajar Aga Wandana (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
The conversion of rubber land to oil palm in the TBM phase has the potential to cause soil degradation due to low organic matter and nutrient availability. low organic matter and increasing risk of erosion on the plant. Not yet producing (TBM). Land conditions are open, without vegetation, which speeds up washing. Nutrients are essential, so a management strategy is needed that maintains soil quality while providing economic benefits to farmers. The intercropping system of corn and soybeans is an important strategy for improving soil quality while increasing economic benefits for oil palm farmers. Study This aim analyze influence system intercropping corn (Zea mays) And soya bean (Glycine max) to change characteristic physique and chemistry land on TBM phase oil palm land resulting from conversion from rubber, and comparing the quality of the soil with the land without intercropping. The study was conducted in the Village of Cape Rambutan, Regency of Kampar, with a purposive sampling design. Sample land taken before and after the implementation of intercropping, with a total of 48 samples analyzed in the laboratory. The parameters observed included soil physical properties (texture, bulk density, porosity, infiltration rate and water-holding capacity). Water level and characteristic soil chemistry (pH, organic carbon, total nitrogen, available phosphorus, CEC, exchangeable bases, and base saturation). Data were analyzed, and the results of the research showed that the application of the corn and soybean intercropping system improved the physical and chemical properties of the soil on oil palm land during the TBM phase, making it a more effective and sustainable land management method. Therefore, this system is recommended to farmers and plantation managers as an alternative to maintain soil quality while increasing the economic value of the land.